Effect of Date of Sowing on the Performance of Drought Tolerant Wheat Genotypes to Spot Blotch at Rampur, Chitwan , Nepal - Aryal, L.; Shrestha, S. M.; K.C., G. B. (International Journal of Applied Sciences and Biotechnology, 2013)
A research was conducted in field to elucidate the response of 20 twenty drought tolerant wheat genotypes to spot blotch. Field experiment was carried out in Agronomy block of IAAS, Rampur, Chitwan in split plot design with three replications, considering 25 November as normal sowing and 15 December as late sowing dates taking them as main factors and genotypes as sub factors. Grain yield was 2.50 t ha-1 on 25 November sowing and 2.03 t ha-1 on 15 December sowing. Similarly thousand kernel weight was 37.50 g on 25 November sowing and 32.82 g on 15 December sowing. Aditya, CSISA DRYT 5204 and CSISA DRYT 5205 had less than 13% grain yield and TKW reduction when sown in late condition also. From the experiment it is concluded that these three genotypes can be sown in late condition as they were resistant to spot blotch and heat stress. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9180 Int J Appl Sci Biotechnol, Vol. 1(4): 266-271